THE EFFECT OF INSTITUTIONAL OWNERSHIP, LEVERAGE AND PROFITABILITY ON EARNINGS MANAGEMENT - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to determine the effect of Institutional Ownership, Leverage and Profitability on Earnings Management in Consumer non-Cyclical Food and Beverage Companies. The population used in this study are 71 Food and Beverage Companies Listed on the Indonesia Stock Exchange. The sample selection was carried out using the purposive sampling method so 39 sample companies are obtained with 195 observation data. The data analysis technique used was multiple linear regression analysis using SPSS software. The result of this study indicate that Institutional Ownership and DAR have no significant effect on Earnings Management, meanwhile ROA have a significant effect on Earnings Management.